A preliminary study on the relationship between symptom severity and age of diagnosis in females versus males with autistic spectrum disorder - Sánchez-Pedroche, Alberto; Aguilar-Mediavilla, Eva; Valera-Pozo, Mario; Adrover-Roig, Daniel; Valverde-Gómez, Magdalena (Frontiers in Psychology, 2025)
In the latest autism observation, autism spectrum disorder (ASD) is more frequently diagnosed in males than in females. Efforts have been made in recent years to detect specific clinical patterns in females, improving their detection and diagnosis. Despite advancements, there are still challenges in detecting ASD in females. This preliminary study explores whether the age at the time of diagnosis of ASD in females is related to a higher severity index compared to male participants. A total of 202 participants (52 females; M = 5.51) in Spain underwent ADOS-2 assessment for ASD clinical severity. The results indicate a significant inverse association between the severity index and the age of diagnosis, which was independent of sex. Despite this, the present results revealed that the age at diagnosis was higher in females compared to males. Further analyses also revealed a tendency toward higher severity levels in females. Factors contributing to this difference in the age of diagnosis of ASD between females and males are discussed concerning the presumed differential characteristics of ASD in females.